Race, Ethnicity, and Disparities in Rheumatology Educational Materials. Issue 9 (22nd June 2022) - Strait, Adrienne; Graf, Jonathan; Margaretten, Mary; Yazdany, Jinoos; Goglin, Sarah
Abstract : Objective: To characterize the representation of dark skin color in clinical images across 4 major rheumatology training resources. Methods: We gathered images of patients with rheumatic diseases from the American College of Rheumatology Image Library, UpToDate, the New England Journal of Medicine Images in Clinical Medicine and Clinical Cases filtered by "Rheumatology, " and the 9th edition of Kelley's Textbook of Rheumatology. Investigators used Fitzpatrick's skin phototypes to independently code images depicting visible skin as "light" (skin types I to IV), "dark" (skin types V to VI), or "indeterminate." The representation of dark skin in clinical images was compared to the representation of Asian, Native American, and Black individuals within the US Census population and within lupus cases nationally. Results: Of the 1, 043 patient images included in the study, 13.4% had dark skin, 84.0% light skin, and 2.6% indeterminate skin color. Dark skin was underrepresented significantly in rheumatology educational materials and lupus images when compared with the representation of Asian, Native American, and Black individuals within the US Census population (13.4% versus 20.6%; χ 2 = 32.8, P < 0.001) and in published studies of patients with systemic lupus erythematous (22.6% versus 44.2%; χ 2 = 20.0, P < 0.001). Conclusion: Darker skin tones are significantly underrepresented in major rheumatology clinical image banks. Improving representation of racial and ethnic minorities in rheumatology education materials can better equip trainees to recognize and diagnose cutaneous manifestations of rheumatic diseases in these groups.